Shed HER2 surrogacy evaluation in primary breast cancer patients: a study assessing tumor tissue HER2 expression at both extracellular and intracellular levels. (19th May 2019) - Fabricio, Aline S.C.; Michilin, Silvia; Zancan, Matelda; Agnolon, Valentina; Peloso, Lucia; Dittadi, Ruggero; Scapinello, Antonio; Ceccarelli, Claudio; Gion, Massimo
Abstract: The aim of the present study was to investigate serum HER2 extracellular domain (ECD) as a putative surrogate marker of the shedding phenomenon of HER2 receptor from the tumor tissue of primary breast cancer (BC) patients. A pilot retrospective study was conducted on 100 matched serum and tissue samples from patients with node-positive primary BC, stage II/III. Analysis of association and concordance between serum HER2 ECD levels (measured by chemiluminescence immunoassay) and the expression in matched tumor tissue of HER2 ECD and intracellular receptor domain (ICD) (determined by immunohistochemistry) were performed. The median serum HER2 ECD level was 9.4 ng/ml and cutoff values were set at 15.2 ng/ml or 13.0 ng/ml. HER2 ICD and ECD were overexpressed in tumor tissue of 19.8% and 6.9% of patients, respectively. Statistically significant associations were found between serum HER2 ECD levels and tissue expression of both HER2 ICD and ECD ( p  < .001; Fisher analysis). Moreover, strong concordances were found between serum HER2 ECD levels and tissue expression of HER2 ICD or ECD (cutoff 15.2 ng/ml: 80 and 92.5%, respectively). Our findings support a role for serum HER2 ECD as a surrogate marker of tissue HER2 status in primary BC, both for HER2 ICD or ECD expression.